Rural Banditry in Bajo Cauca, Magdalena Medio and Nordeste in Antioquia (Colombia), 1953-1958 [Bandolerismo Rural en el Bajo Cauca, Magdalena Medio y el Nordeste Antioqueño (Colombia), 1953-1958] - Henao-Holguin, D (Universidad Nacional de Colombia, 2015)
This article attempts to contribute to the discussion about the rural banditry from the regional analysis perspective. It explores the areas of Bajo Cauca, Norwest and Magdalena Medio in Antioquia (Colombia) between 1953 and 1958. In those years the bandit appears in the regional context after the breakdown of the liberal guerrillas of the first phase of La Violencia (1949-1953). Thus, it acquires characteristics that differ from the concept of social banditry proposed by Eric Hobsbawm. This paper shows that the contextual analysis allows us to observe the peculiarities and the nature of the phenomenon. It has different profiles that are beyond general explanations.